Artushof und Artusliteratur - Däumer, Matthias 1976-; Dietl, Cora 1967-; Wolfzettel, Friedrich 1941- (De Gruyter, 2010)
The court of King Arthur, the center of the Arthurian romances that were so popular in the Middle Ages, is illuminated anew in this book from an interdisciplinary perspective as an institution which is fictionally staged, stabilized and problematized. The book explores the forces, figures and positions that constitute or endanger the court as a picture of society in miniature or as a literary experiment. Finally, the contributions critically question the <ideality> of the court of King Arthur and investigate the function and reception of the court even in contexts remote from courts.
Keywords: Geschichte; Artusepik; Hof -- Motiv; Konferenzschrift -- 2008 -- Rauischholzhausen; Aufsatzsammlung